ANALYSIS METHODS OF INFORMATION PROTECTION IN A RELATIONAL DATABASE MONGODB - Мелешко, О. О.; Шмир, М. А. (Science-based technologies, 2016)
The main resolution of this article is to analyze the possible methods of information protection in non-relational database MongoDB. In this article the basic methods of unauthorized access to information; investigated material domestic and foreign authors; considered standards that are used to provide cryptographic system stability; the practical recommendations on database administration; The proposals for improving the security features of the system by using the new software. Also defined methods possible unauthorized access to MongoDB. Based on the analysis the main mechanisms to protect against unauthorized access, and how to improve them. Because MongoDB - one of the best non-relational document oriented database that uses a variety of mechanisms crypto protection. It is proved that the main cause is ignorance hacking systems administrators of all defense mechanisms.